Factors Related to Postnatal Care Utilization in Indonesia in 2018: An Ecological Study - Eni Purwaningsih; Hario Megatsari; Agung Dwi Laksono; Mursyidul Ibad (Indian Journal of Forensic Medicine & Toxicology, 2021)
Postnatal care is very crucial in the postnatal period because it is a critical period for babies. This study aimsto analyze the factors related to postnatal care utilization (1st neonatal visits) in Indonesia. The ecologicalanalysis was conducted using secondary data from the Ministry of Health of the Republic of Indonesiareport in 2018. All provinces were taken as samples. Apart from postnatal care utilization, 5 other variablesanalyzed as independent variables were the ANC 1st visit, ANC 4th visits, poverty depth index, percentageof health centers with sufficient midwives, and the ratio of gynecologist per 100,000 population. The resultsshow there was a tendency for a positive relationship between ANC 1st visit and 1st neonatal visit. The higherthe ANC 1st visit coverage, the higher the 1st neonatal visit coverage (p = 0.034). Meanwhile, there was alsoa trend towards a positive relationship between the ANC 1st visit and the 1st neonatal visit. The higher thecoverage of the ANC 4th visit, the higher the coverage of the 1st neonatal visit (p = 0.040). Moreover, povertydepth index, percentage of health centers with sufficient midwives, and the ratio of gynecologist per 100,000population were found to have no significant correlation with 1st neonatal visits. It could be concluded thatfrom the 5 independent variables analyzed, 2 variables were proven to be ecologically positively related topostnatal care utilization (1st neonatal visit), namely ANC 1st visit and ANC 4th visit.